Various editing forms of documents for texts of national science-technology development - Long, Hoang Xuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Definition of relations between contents and editing forms of national science-technology (S&T) development planning documents is very meaningful for activities of editing, implementing and amending works for plans. Contents of plans for S&T development can be presented in various editing forms of texts. Contents of plans for S&T development can combine with other contents in editing forms of texts for S&T strategies, plans for S&T development and S&T plans. At the same time, there exist various editing forms of texts of plans: global-individual, integrated-independent. Every editing form of texts has its own advantages and disadvantages. For actual situation in Vietnam, a particular attention should be paid to individual and independent editing forms of texts for plans of S&T development. Code: 13052701